The Effects of Spiritual Intelligence and Organizational Citizenship Behavior to Employees Performance: Study at Sharia Banks in Gorontalo Province - HM, Muhdar (Economica: Jurnal Ekonomi Islam, 2018)
The employees? existence as an organizational locomotive need to get attention for management because, it is employees who make the organization perform well. Spiritual intelligence and organizational citizenship behaviour (OCB) are known to have effect for improving employee performance. To see this effect, then research was conducted at Sharia Bank in Gorontalo Province with the aim of analyzing and describing the effect of: spiritual intelligence on OCB, spiritual intelligence on employee performance, OCB on employee performance, and spiritual intelligence on employee performance through OCB. The findings of this study are spiritual intelligence had positive and significant effect on OCB. OCB has positive and significant effect on employee performance. Spiritual intelligence has positive and insignificant effect on employee?s performance, but spiritual intelligence has positive and significant effect for employee performance through OCB.Keberadaan karyawan sebagai lokomotif organisasi perlu mendapat perhatian oleh manajemen karena karyawan yang membuat organisasi berkinerja baik. Kecerdasan spiritual dan perilaku kewargaan organisasional (OCB) diketahui memiliki implikasi untuk meningkatkan kinerja karyawan. Untuk melihat implikasi ini, maka dilakukan penelitian pada Bank Syariah di Provinsi Gorontalo dengan tujuan menganalisis dan menggambarkan implikasi dari: kecerdasan spiritual terhadap OCB, kecerdasan spiritual terhadap kinerja karyawan, OCB terhadap kinerja karyawan, dan kecerdasan spiritual terhadap kinerja karyawan melalui OCB. Hasil penelitian menunjukkan bahwa kecerdasan spiritual memiliki implikasi positif dan signifikan terhadap OCB. OCB berimplikasi positif dan signifikan terhadap kinerja karyawan. Kecerdasan spiritual berimplikasi positif dan tidak signifikan terhadap kinerja karyawan, tetapi kecerdasan spiritual berimplikasi positif dan signifikan terhadap kinerja karyawan melalui OCB